Study of Dielectric Barrier Discharge in Air and Estimation of Electron Density and Energy Deposition - Thapa, Bhesh Bahadur; Tyata, Raju Bhai (Journal of Science and Engineering, 2019)
This paper reports the electrical behaviors of atmospheric pressure plasma reactor with Dielectric Barrier Discharge (DBD) in air medium. The DBD discharge was generated in air at atmospheric pressure using Disc Electrode Geometry (DEG) reactor powered by ac voltage (0-7kV) at a frequency of 24kHz. The glass plates of thickness 1.0mm and 3.0mm were used as dielectric. The current-voltage characteristics were studied for two air gap of 2.0mm and 3.0mm by varying the applied voltages. The numbers of filamentary micro discharges were found as increased in each half cycle with increase in power. The observations of Lissajous figure of applied voltage versus electric current was used for measuring energy deposited by discharge and also compared with calculated value. Lissajous figures clearly show that the energy deposited by discharge was dependent on applied voltage. The electron density of discharge was measured by power balance method. Electron density was found in the order of 1017 per cubic meter.